Efficacy and safety of daily home-based transcranial direct current stimulation as adjunct treatment for bipolar depressive episodes: Double-blind sham-controlled randomized clinical trial - Lee, Jangwon; Lee, Chan Woo; Jang, Yoonjeong; You, Ji Seon; Park, Yun Seong; Ji, Eunjeong; Yu, Hyeona; Oh, Sunghee; Ryoo, Hyun A.; Cho, Nayoung; Park, Ji Yoon; Yoon, Joohyun; et al. (Frontiers in Psychiatry, 2022)
Background Although transcranial direct current stimulation (tDCS) is known to be a promising therapeutic modality for unipolar depression, the efficacy and safety of tDCS for bipolar depressive episodes (BD) are still unknown and clinical trials of home-based tDCS treatment are scarce. As a result, we set out to investigate the efficacy and safety of home-based tDCS for the treatment BD. Methods Participants (n = 64), diagnosed as bipolar disorder as per the diagnostic and statistical manual of mental disorders (DSM-5), were randomly assigned to receive tDCS. Hamilton Depression Rating Scale (HDRS-17) scores were measured at the baseline, week 2, 4, and 6, and home-based tDCS (for 30 min with 2 mA) was self-administered daily. Results Of the 64 patients (15.6% bipolar disorder I, 84.4% bipolar disorder II), 41 patients completed the entire assessment. In the intention-to-treat analysis, time-group interaction for the HDRS-17 [F(3, 146.36) = 2.060; p = 0.108] and adverse effect differences between two groups were not statistically significant, except the pain score, which was higher in the active group than the sham group (week 0–2: p < 0.01, week 2–4: p < 0.05, and week 4–6: p < 0.01). Conclusion Even though we found no evidence for the efficacy of home-based tDCS for patients with BD, this tool was found to be a safe and tolerable treatment modality for BD. Clinical trial registration [https://clinicaltrials.gov/show/NCT03974815], identifier [NCT03974815].